Porcine Rotaviruses: Epidemiology, Immune Responses and Control Strategies - Vlasova, Anastasia N.; Amimo, Joshua O.; Saif, Linda J. (MDPI, 2017)
Rotaviruses (RVs) are a major cause of acute viral gastroenteritis in young animals and children worldwide. Immunocompetent adults of different species become resistant to clinical disease due to post-infection immunity, immune system maturation and gut physiological changes. Of the 9 RV genogroups (A–I), RV A, B, and C (RVA, RVB, and RVC, respectively) are associated with diarrhea in piglets. Although discovered decades ago, porcine genogroup E RVs (RVE) are uncommon and their pathogenesis is not studied well. The presence of porcine RV H (RVH), a newly defined distinct genogroup, was recently confirmed in diarrheic pigs in Japan, Brazil, and the US. The complex epidemiology, pathogenicity and high genetic diversity of porcine RVAs are widely recognized and well-studied. More recent data show a significant genetic diversity based on the VP7 gene analysis of RVB and C strains in pigs. In this review, we will summarize previous and recent research to provide insights on historic and current prevalence and genetic diversity of porcine RVs in different geographic regions and production systems. We will also provide a brief overview of immune responses to porcine RVs, available control strategies and zoonotic potential of different RV genotypes. An improved understanding of the above parameters may lead to the development of more optimal strategies to manage RV diarrheal disease in swine and humans.